Are Students' Basic Psychological Needs Fulfilled in Remote Learning Environments?: A Mixed Methods Study - Lindsay M Griendling; Victoria J. VanUitert; Sean D. McDonald (Middle Grades Review, 2022)
Self-determination theory (SDT) posits that three basic psychological needs (i.e., autonomy, competence, and relatedness) must be fulfilled to promote positive outcomes among individuals participating in social environments. Teachers can provide supports to fulfill these needs within classroom environments to help them become autonomously motivated to engage in tasks and activities. Unfortunately, school closures and the shift to remote learning during the COVID-19 pandemic may have challenged teachers’ ability to create need-supportive classroom environments due to issues such as reliable access to technology, teacher preparedness in facilitating remote learning, and negative impacts to mental health and well-being. However, the extent to which these challenges impacted students’ basic need fulfillment has not been investigated to date. Thus, the purpose of this convergent mixed methods study is to evaluate remote teaching from multiple perspectives in order to gain a more complete understanding of the types of strategies that are employed in remote classes, as well as the extent to which teachers, students, and parents perceive remote learning environments as being supportive of students’ autonomy, competence, and relatedness needs. Teachers (n = 17) from two middle schools were observed providing remote instruction, and they, along with students (n = 11) and parents (n = 10), participated in a survey and interviews that provided further insight into basic need fulfillment in remote environments. Implications for the field are discussed.
Keywords: Remote learning; self-determination theory; adolescence; middle school